The relationship between entrepreneurial competencies, innovation and SMEs performance in northern Malaysia - Yusof, Mohd Sufli; Mohd Shariff, Mohd Noor (2017)
Small and Medium Enterprises (SMEs) received great attention on its contributions in the policies of economic and social development either in the countries that have developed or in developing countries.The purpose of this study is to examine the relationship between entrepreneurial competency, innovation and SMEs performance in Northern Malaysia.A random sampling technique was used on 97 usable questionnaires and data was analyzed by SPSS 19.Statistically, the results confirmed that entrepreneurial competency has significant positive relationship with firm performance; whereas, innovation does not have any significant relationship with firm performance. However, there is a significant combined effect of entrepreneurial competency and innovation on firm performance.Finally, this study will provide important information on the management and innovation practices of entrepreneurship among SMEs in Malaysia.